Integration of vector physics learning with the qur'an: investigating the effect of worked example (WE) in increasing the value of spiritual character in higher education - Mitra Yadiannur; Rahmah Rahmah; Sulaiman Sulaiman (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
This study aims to measure the effectiveness of the Qur'an integrated worked example vector to increase the value of spiritual characters seen from the partial eta square in the Anava Mixed Design - General Linear Model (GLM). This type of research is quantitative research with experimental research methods. The research design used was the Pretest-Posttest Mixed Design with the experimental group - control. The samples used were 20 students each in both groups. The sampling technique used is cluster random sampling. The test instrument used was a spiritual character score test of 20 multiple choice questions that were validated by 3 expert judgments in the field of character education, 2 physics lecturers, 1 religion lecturer, and 4 colleagues and obtained Aiken's V score of 0.83 with the category very good. Empirical tests were also carried out to see the level of reliability and feasibility of the item questions. A total of 185 students were involved. The reliability result is 0.97 with a very high category and 20 questions are suitable for use based on the output of the QUEST program. The results showed that there was a significant improvement difference between the control and experimental classes, where the worked example was able to increase the value of spiritual characters with an effectiveness of 61% based on the partial eta square output in the experimental class while in the control group an effectiveness of 10 percent was obtained.